2005
DOI: 10.1158/1541-7786.mcr-05-0088
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism of COOH–Terminal Binding Protein–Mediated Repression

Abstract: The E2F4 and E2F5 proteins specifically associate with the Rb-related p130 protein in quiescent cells to repress transcription of various genes encoding proteins important for cell growth. A series of reports has provided evidence that Rb-mediated repression involves both histone deacetylase (HDAC) -dependent and HDAC-independent events. Our previous results suggest that one such mechanism for Rb-mediated repression, independent of recruitment of HDAC, involves the recruitment of the COOH-terminal binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…It is possible that CtBP1, unlike CtBP2, uses additional HDAC-independent mechanisms (see below). Previous reports have suggested that CtBP1 antagonizes the activities of global trans activators such as p300/CBP and P/CAF (26,34,48).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that CtBP1, unlike CtBP2, uses additional HDAC-independent mechanisms (see below). Previous reports have suggested that CtBP1 antagonizes the activities of global trans activators such as p300/CBP and P/CAF (26,34,48).…”
Section: Discussionmentioning
confidence: 98%
“…The potential role of CtBP1 in targeting the sumoylation machinery to the chromatin is an attractive possibility and remains to be explored. CtBP1 has been reported to antagonize the activity of positive transcription factors such as p300/CBP (26,34,48). Since sumoylation of p300 has been reported to reverse its transcriptional function (14), the possibility that CtBP1 inhibits the activity of p300/CBP through sumoylation also remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This model is suggested by the finding that K10R and 3KR mutants of CtBP2 were more active in repression of the E-cadherin promoter. There is a precedent for such a model, as CtBP has been reported to sequester and inhibit the transcriptional activities of positive transcriptional regulators such as p300/CBP (25,48,49) and nuclear ␤-catenin (50). Alternatively, cytoplasmically localized non-acetylated CtBP2 may help regulate cytoplasmic functions, which may have an indirect effect on E-cadherin promoter.…”
Section: Discussionmentioning
confidence: 99%
“…In CtBP1, the existence of a protein interaction surface other than the PXDLSbinding pocket has been inferred (51). Similarly, regions of p300, in addition to the bromodomain have been implicated in interaction with CtBP1 (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…This shows a complementary mechanism by which CtBP represses transcription. [14][15][16] CtBP proteins have structural similarities to NAD + -dependent D-hydroxyacid dehydrogenases. They form homo-and heterodimers with each subunit consisting of a nucleotide-binding domain (capable of binding NAD + or NADH) and the substrate-binding domain at the N-terminus including the cleft that interacts with the PXDLS peptide.…”
Section: Introductionmentioning
confidence: 99%